STRATEGY THROUGH SOCIAL MEDIA TO INCREASE NEW STUDENT INTEREST - Najiah, Layli; Faiz, Faiz; Huda, Nurul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Educational marketing management is a series of activities involving analysis, planning, implementation, and evaluation. The purpose of this study was to determine: (1) educational marketing planning at MTs ZaHa 3 Probolinggo, (2) implementation of educational marketing at MTs ZaHa 3 Probolinggo, and (3) evaluation of educational marketing at MTs ZaHa 3 Probolinggo. This study uses a qualitative method with a descriptive approach and analysis. Data were collected through observation, interview, and documentation techniques. The subjects of the study were the principal and the Vice Principal for Public Relations of MTs ZaHa 3 Probolinggo. Based on the results of the study, educational marketing management at this school needs to be implemented with good management, both in planning, implementation, and evaluation. Planning at school is carried out through meetings or meetings with related parties to design programs that will be implemented in the future, including determining the time, place, and targets to be achieved. Implementation of educational marketing is carried out through various promotional methods, such as distributing brochures and socializing to target schools. The evaluation stage is carried out once every semester to ensure whether the implementation of marketing is in accordance with the initial plan or still needs adjustment.